Tackling a Problematic Bullying; A Strategic Behavioral Management Intervention Based on Pesantren - Akmal Mundiri; Lulus Ariska; Hasan Jali (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to examine the role of Islamic boarding schools (pesantren) in addressing bullying by implementing behavioral management interventions at Nurul Jadid Islamic Boarding School. A qualitative case study approach was used to explore the factors influencing bullying and the intervention model implemented. Information sources consisted of foster parents, the Head of the Regional Guidance and Counseling (BK), and security and order officers at the Islamic boarding school. Data collection was conducted through observation, in-depth interviews, and documentation. Data were analyzed using data reduction, display, and verification stages to obtain valid results. This research found that behavioral management strategies in dealing with bullying in Islamic boarding schools are carried out through punishment, character-building, character building socialization, spiritual approaches, role models, and counseling. Thus, the findings of this study indicate that Islamic boarding schools can play a significant role in developing anti-bullying character through practical guidance and behavioral management strategies.